Shaping the Character of Christ in Children with Special Needs: The Role of Sunday School Teacher in Pentecostal Churches - Niansari, Ruth Madhu; Manurung, Kosma (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
This study aims to form the character of Christ in children with special needs so that in their social behavior, they deserve to be treated the same as other children in their right to receive education, including in the church environment. This study attempts to frame the role of Sunday school teachers in instilling the character of Christ in children with special needs in the Pentecostal church environment. The use of qualitative descriptive methods and literature reviews in working on this article is expected to provide an overview of children with special needs, the importance of the character of Christ for children, and the role of Sunday school teachers in instilling the character of Christ in children with special needs in the Pentecostal church environment. It is concluded that Sunday school teachers will play their role optimally when they must be role models, prepare a curriculum with inclusive education that is easy for children to understand, build good communication relationships, and become collaborators for parents or other parties related to children. So that each church also has a special service or mentoring program for children with special needs. This means that in worship, Sunday school teachers have a vital role in forming the Character of Christ in children with special needs by prioritizing fair and wise behavior so that they can inspire parents and other children present.